Is body mass index ≥50 kg/m(2) a predictor of higher morbidity for patients who have undergone laparoscopic sleeve gastrectomy? - Bamehriz, Fahad (Saudi J Anaesth, 2018)
BACKGROUND: Super-morbid obese (SMO) patients (body mass index [BMI] >50 kg/m(2)) carry a higher risk for bariatric surgery. Despite several studies addressing this patient group, the number of patients included tends to be relatively small. METHODS: We reviewed 708 patients who underwent laparoscopic sleeve gastrectomy between 2009 and 2015 and compared the outcome of SMO (BMI ≥50 kg/m(2)) patients with MO (BMI <50 kg/m(2)) patients. RESULTS: Of 708 patients, 217 were SMO and 491 were MO. Both groups had homogeneous baseline characteristics and comorbidities, except sleep apnea which was higher in SMO group. There was no significant difference for the duration of operation, length of stay, or recovery room time. The mean number of trocars was four for both groups. There were no conversions to open or documented intraoperative complications in either group. Postoperative complications occurred in 13 (6%) SMO patients (3 patients with leakage and 10 with bleeding). Postoperative complications occurred in 21 (4.3%) MO patients (11 patients with leakage and 10 with bleeding). No reoperation was done in both groups. There was no surgical mortality. CONCLUSION: We detected no significant difference in the duration of operation and intra- or postoperative complication between SMO and MO groups. The possibility of the safety of this procedure in SMO group can be adopted.